SOCIAL MEDIA AS A TOOL FOR PROMOTING SCIENCE - Azhibekova Zh.; Suranshin A.; Berbolatov M. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
Social media platforms have transformed how scientific knowledge is produced, disseminated, and perceived by both peers and the public. This paper examines the roles, benefits, challenges, and good-practice recommendations for using social media to promote science. Using a narrative review of recent literature and policy statements, we summarize evidence that social media increases research visibility, accelerates dissemination, supports public engagement, and provides alternative impact measures (altmetrics). At the same time, social platforms present risks: rapid spread of misinformation, lack of traditional peer review, ethical/privacy concerns, and uneven access across audiences. We propose practical guidelines for researchers and institutions to leverage social media effectively — clear communication training, institutional policies, use of evidence-based formats (e.g., short videos, visual abstracts), and routine evaluation of outreach impact. When used responsibly, social media is a powerful complement to traditional scholarly communication and a crucial tool for modern science promotion.
Keywords: social media; science communication; altmetrics; misinformation; public engagement